Heterogeneity in the photoprotective capacity of three Antarctic diatoms during short-term changes in salinity and temperature - Petrou, K; Doblin, MA; Ralph, PJ (2011)
The Antarctic marine ecosystem changes seasonally, forming a temporal continuum of specialised niche habitats including open ocean, sea ice and meltwater environments. The ability for phytoplankton to acclimate rapidly to the changed conditions of these environments depends on the species' physiology and photosynthetic plasticity and may ultimately determine their long-term ecological niche adaptation. This study investigated the photophysiological plasticity and rapid acclimation response of three Antarctic diatoms-Fragilariopsis cylindrus, Pseudo-nitzschia subcurvata and Chaetoceros sp.-to a selected range of temperatures and salinities representative of the sea ice, meltwater and pelagic habitats in the Antarctic. Fragilariopsis cylindrus displayed physiological traits typical of adaptation to the sea ice environment. Equally, this species showed photosynthetic plasticity, acclimating to the range of environmental conditions, explaining the prevalence of this species in all Antarctic habitats. Pseudo-nitzschia subcurvata displayed a preference for the meltwater environment, but unlike F. cylindrus, photoprotective capacity was low and regulated via changes in PSII antenna size. Chaetoceros sp. had high plasticity in non-photochemical quenching, suggesting adaptation to variable light conditions experienced in the wind-mixed pelagic environment. While only capturing short-term responses, this study highlights the diversity in photoprotective capacity that exists amongst three dominant Antarctic diatom species and provides insight into links between ecological niche adaptation and species' distribution. © 2011 Springer-Verlag.